Produksi Metabolit Utama (-)-Citrinin, pada Kultur Jamur Endofit Penicillium sp dari Tanaman Teh - Andria Agusta; Yuliasri Jamal (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
Endophytic fungi have been recognized as source of broad range biological active metabolites with high chemical structure diversity. The purpose of this research is to isolate and characterize major metabolite produce by the endophytic fungi Penicillium sp isolated from a tea plant. Cultivation of endophytic fungus Penicillium sp (AB2245443) in liquid medium PDB on a rotary shaker at 100 rpm, temperature 25 – 30oC for 7 days, produced a yellow metabolite. Separation of metabolite through chromatography technique and followed by chemical structure elucidation based on MS, IR, NMR spectra and published data showed that the yellow metabolite is (-)-citrinin.